Highly birefringent microstructured fiber selectively filled with lossy material - Ertman, Slawomir; Nasilowski, Tomasz; Wolinski, Tomasz R.; Thienpont, Hugo (Photonics Letters of Poland, 2009)
Photonic crystal fibers (PCFs) filled with various substances can be used as all-in-fiber tunable devices. Due to their optical anisotropic properties, liquid crystals (LCs) are one of the best solutions for these devices. However, numerical modeling and design may be a very challenging task in this case if LC anisotropy is considered. Moreover, LCs are characterized by much higher losses than silica glass and it is not clear how it will affect the modal properties. In this paper we investigate theoretically highly birefringent PCFs selectively filled with lossy materials characterized by a wide range of extinction coefficients. Full Text: PDF References: P.S.J. Russel,"Photonic-Crystal Fibers", J. Lightwave Technol., Vol. 24, pp. 4729-4749, 2006 [CrossRef] T. T. Larsen et al.,"Optical devices based on liquid crystal photonic bandgap fibres", Opt. Express 11, 2589-2596 (2003) [CrossRef] M.W. Haakestad et al.,"Electrically tunable photonic bangap guidance in a liquid-crystal-filled photonic cystal fiber", IEEE Phot. Techn. Lett. 17, 819-821 (2005). [CrossRef] F. Du et al., "Electrically tunable liquid-crystal photonic crystal fiber”, Appl. Phys. Lett. 85, 2181-2183 (2004) [CrossRef] T. Alkeskjold et al., "All-optical modulation in dye-doped nematic liquid crystal photonic bandgap fibers", Opt. Express 12, 5857-5871 (2004) [CrossRef] T. R. Woliński et al., "Influence of temperature and electrical fields on propagation properties of photonic liquid crystal fibers", Measurement Science and Technology 17, 985–991 (2006) [CrossRef] T. R. Woliński et al., "Polarization effects in photonic liquid crystal fibers", Measurement Science and Technology, 18, 3061-3069 (2007) [CrossRef] N. M. Litchinitser et al.,"Antiresonant reflecting photonic crystal optical waveguides", Opt. Lett. 27, 1592-1594 (2002) [CrossRef] P. Lesiak et al.,"Temperature tuning of polarization mode dispersion in single-core and two-core photonic liquid crystal fibers", Opto-Electron. Rev. 15, 27-31 (2007) [CrossRef] S. Ertman et al.,"Light propagation in highly birefringent photonic liquid crystal fibers", Opto-Electron. Rev. 17, 104-109 (2008) [CrossRef] D. C. Zografopoulos et al.,"Photonic crystal-liquid crystal fibers for single-polarization or high-birefringence guidance", Opt. Express 14, 914-925 (2006) [CrossRef] J. Sun et al.,"Analysis of photonic crystal fibers infiltrated with nematic liquid crystal", Optics Communications 278, 66-70 (2007) [CrossRef] J. Sun and C.C. Chan,"Hybrid guiding in liquid-crystal photonic crystal fibers", J. Opt. Soc. Am. B., vol. 24, no. 10, 2640-2646 (2007) [CrossRef] F. Brechet et al.,"Complete analysis of the characteristics of propagation into photonic crystal fibers, by the finite element method", Opt. Fiber Technol. 6, 181–191 (2000) [CrossRef] G. Tartarini et al., "Polarization properties of elliptical-hole liquid crystal photonic bangap fibers", Journal of Lightwave Technology vol. 25, no. 9, 2522-2530 (2007) [CrossRef] M. Saito et al., "Measurement of the efractive-index spectrum for birefringent and absorptive liquids", Appl. Opt. 37, 5169–5175 (1998) [CrossRef] Masahito Oh-e et al., "Liquid Crystal Colloids Studied by THz Time-Domain Spectroscopy", Mol. Cryst. Liq. Cryst., Vol. 480, pp. 21–28, (2008) [CrossRef] M. Saito et al., "Complex refractive-index spectrum of liquid crystal in the infrared", Appl. Opt. 37, 2366–2372 (2003) Handbook of Optical Constants of Solids, Academic Press, Boston, 1991 [CrossRef] Handbook of Optical Constants of Solids, Academic Press, Boston, 1991 M. Szpulak et al., Opt. Comm. 239 (2004) 91–97